Kajian Feminisme dalam Novel Cinta di Dalam Gelas karya Andrea Hirata - Alfin Maqfiroh; Muhammad Hifdil Islam; Ahmad Ilzamul Hikam (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study intends to describe the elements of feminism in Andrea Hirata's novel Love in a Glass. In this study used qualitative research. Reading and note-taking techniques were used to collect data. Novel Cinta in a Glass is examined using content analysis techniques as part of the data analysis process. Data validation techniques use persistence. The results to be revealed are violence, oppression, hard work, and resistance from a feminist point of view against the novel Cinta in the Glass through the characters Enong or Maryamah.